Geological and Geophysical Studies of the Ninety East Ridge: A Brief Review - Kavya Aravind; Neelakantan Ravindran Nisha (International Journal of Marine Life, 2024)
The Indian Ocean serves as a unique laboratory for studying the impact of both global and regional stressors on environmental changes over various geological epochs. Its distinct hydrological conditions and geographical location make it an ideal focal point for research into these phenomena. Of particular interest within the Indian Ocean is the Ninety East Ridge (NER), which holds significance as the world's longest linear rise. Researchers have long hypothesized that the Ninety East Ridge owes its origin to a hotspot trace influenced by the Kerguelen plume. However, a comprehensive review of geological and geophysical research along the NER is needed to gain a deeper understanding of its tectonics, evolution, geological setting, and provenance. This review encompasses the Ridge's entire history, spanning from the Paleocene to the present day. Through an analysis of various datasets and research findings, this review aims to elucidate the processes that have shaped the Ninety East Ridge over millions of years. By examining sediment cores, seismic profiles, and other geological data, researchers can reconstruct the Ridge's formation and subsequent evolution. This includes investigating the role of tectonic activity, sea level changes, and climatic variations in shaping the NER. Furthermore, the review will explore the implications of the Ninety East Ridge's formation for broader geological and environmental studies. Understanding the processes that govern the development of features like the NER can provide valuable insights into global tectonic dynamics, paleoclimate patterns, and the distribution of marine life throughout Earth's history. Overall, this comprehensive review seeks to consolidate existing knowledge about the Ninety East Ridge while also highlighting avenues for future research. By synthesizing data from multiple disciplines, it aims to contribute to our broader understanding of the Indian Ocean's geological history and its significance in the context of global environmental change.
Keywords: Evolution; Genesis; Ninetyeast Ridge; Tectonics